Anxiety and medication use among medical students: Prevalence, associated factors, and implications for medical training - Rodrigo Gonçalves Corrêa; Fernanda Tobar Lo Ré Chambray; Pedro Lucarelli Gonçalves De Oliveira; Júlia Manfré Moraes Dutra; Luana Mendes Da Silva; Sarah Dalilah Broering; Caique Sousa Silva (International Health Sciences Review, 2026)
Anxiety is highly prevalent during medical training, but its relationship with medication use is more complex than a simple association between distress and self-medication. This narrative and critical review examined the prevalence and determinants of anxiety among medical students, patterns of prescribed and non-prescribed psychotropic use, and the implications of both phenomena for academic and professional formation. PubMed/MEDLINE and SciELO were searched in 2026 using combinations of terms related to medical students, anxiety, psychotropic drugs, antidepressants, anxiolytics, benzodiazepines, stimulants, self-medication, academic performance, sleep, stigma, and help-seeking. Meta-analyses consistently indicate that roughly one third of medical students report clinically relevant anxiety symptoms, although estimates vary substantially with instruments, settings, and academic periods. Medication studies show equally heterogeneous patterns: some document appropriate psychiatric treatment, whereas others identify psychotropic self-medication, benzodiazepine use for academic stress, or stimulant use for cognitive enhancement. Academic overload, examinations, poor sleep, limited support, stigma, and barriers to confidential care repeatedly appear as associated factors. Anxiety and maladaptive medication use may impair concentration, sleep, academic performance, and help-seeking, but most evidence is cross-sectional and does not establish causality. Medical schools should combine accessible confidential care with curricular, cultural, and medication-safety strategies rather than relying on individual resilience alone.